2020
DOI: 10.1101/2020.04.21.054304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytotoxic lymphocytes use mechanosurveillance to target biophysical vulnerabilities in cancer

Abstract: 33 34 Immune cells identify cancer cells by recognizing characteristic biochemical 35 features indicative of oncogenic transformation. Cancer cells have characteristic 36 mechanical features, as well, but whether these biophysical properties also contribute to 37 destruction by the immune system is not known. In the present study, we found that 38 enhanced expression of myocardin related transcription factors (MRTFs), which promote 39 migration and metastatic invasion, paradoxically compromised lung colonizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…Although our focus here is on the role of stiffness sensing in priming of naïve T cells, we find that effector CD8 + T cells also exhibit stiffness-dependent degranulation; stiffness-dependent cytokine production by CTLs has also recently been reported ( Tello-Lafoz et al, 2020 ). Similarly, Saitakis et al have shown that restimulating CD4 + effector T cells on surfaces of different stiffness induces differential gene expression and cytokine production ( Saitakis et al, 2017 ).…”
Section: Discussionmentioning
confidence: 86%
“…Although our focus here is on the role of stiffness sensing in priming of naïve T cells, we find that effector CD8 + T cells also exhibit stiffness-dependent degranulation; stiffness-dependent cytokine production by CTLs has also recently been reported ( Tello-Lafoz et al, 2020 ). Similarly, Saitakis et al have shown that restimulating CD4 + effector T cells on surfaces of different stiffness induces differential gene expression and cytokine production ( Saitakis et al, 2017 ).…”
Section: Discussionmentioning
confidence: 86%
“… Mechanistic studies are required to determine the extent to which stiffness of target cells influences T cell effector functions. More recently, Tello-Lafoz et al discovered that increased cellular stiffness resulting from enhanced expression of myocardin-related transcription factor (MRTF) in metastatic cancer cells enhanced their susceptibility to CTL-mediated killing . Sensing of this biomechanical vulnerability by T cells, a process termed “mechanical immunosurveillance”, offers a novel perspective on the biomechanical nature of T cell immunity, as well as a possible target for mechanical immunoengineering of T cells.…”
Section: Passive Mechanical Cues For Mechanical Immunoengineering Of ...mentioning
confidence: 93%